Pengembangan Sistem Layanan Penerimaan Peserta Didik Baru Berbasis Web - Riyanto, Andi Dwi; Charis Prasetya, Subani; Alif Jamaluddin, Ilham (P3M Politeknik Negeri Cilacap, 2024)
In today's digital era, technology has become an important element in various aspects of life, including in the education sector. YPE Kroya Vocational High School in Cilacap, which currently has a manual new learner registration process, faces challenges in managing registration data that can lead to errors such as incorrect name writing and column placement. To overcome this problem, the research team developed a website-based New Learner Admission service system. This system is designed to facilitate the registration and selection process while improving efficiency in data management. The development of this system follows the System Development Life Cycle (SDLC) method, resulting in an effective website-based PPDB service system. This system not only facilitates the registration process and data management of prospective students but also provides solutions to problems that exist in the conventional registration process. System testing has been conducted through Black Box and User Acceptance Testing (UAT) methods validating the reliability and usability of the system. The results of the UAT analysis showed that the system received a very positive assessment from the users with an average score of 4.48 (90%) for Design, 4.44 (89%) for Efficiency, and 4.42 (88%) for Service.